(untitled) (Ameghiniana, 2013)
A new genus and species of Furnariidae, Pseudoseisuropsis nehuen, from the Miramar Formation (Lower-Middle Pleistocene), Miramar, Buenos Aires, Argentina, is described. Morphological similarity with species of the genus Pseudoseisura (subfamily Phylidorinae) is suggested. Terrestrial habits are inferred on the basis of the tarsometatarsus morphology. It probably occupied open habitats in arid to semiarid environments.